Novel cost-effective design for bio-volatilization studies in photosynthetic microalgae exposed to arsenic with emphasis on growth and glutathione modulation - Upadhyay, Atul K.; Mallick, Shekhar; Singh, Ranjan; Singh, Lav; Singh, Nitesh; Mandotra, S. K.; Singh, Arpit; Srivastava, Ravi Prakash; Pandey, Shivaraman; Saxena, Gauri (Frontiers in Microbiology, 2023)
A novel laboratory model was designed to study the Arsenic (As) biotransformation potential of 30 microalgae Chlorella vulgaris, Nannochloropsis sp. and cyanobacteria Anabaena doliolum. Algae 31 were treated under different concentration of As (III) to check its growth, toxicity optimization 32 and volatilization potential. Results revealed that alga Nannochloropsis sp. was better adopted in 33 term of growth rate and biomass than C. vulgaris and A. doliolum. Algae grown under As (III) 34 environment can tolerate upto to 200μM As (III) with moderate toxicity impact. Further, the 35 present study revealed the biotransformation capacity of algae A. doliolum, Nannochloropsis sp. 36 and Chlorella vulgaris. Microalgae Nannochloropsis sp volatilized large maximum amount of As 37 (4393 ng), followed by C. vulgaris (4382.75 ng) and A. doliolum (2687.21 ng) respectively, after 38 21 d. The present study showed that As (III) stressed algae conferred resistance and provide 39 tolerance through high production of glutathione content and As-GSH chemistry inside cells. Thus, 40 algal biotransformation potential of volatilization may contribute in global As reduction, 41 biogeochemistry and detoxification.